Debt Peonage in Granada, Nicaragua, 1870-1930: Labor in a Noncapitalist Transition - Dore, Elizabeth (Hispanic American Historical Review, 2003)
Revisits the debt peonage debate, central to understanding Latin American transitions to capitalism, particularly in Diormo, Granada, Nicaragua. Differences between capitalist and noncapitalist societies according to Karl Polanyi and Robert Brenner; Land peasantry in Diriomo; Legislation enacted to compel peasants to work in plantation agriculture.
History
Keywords: BRENNER; Robert; 1943-; Nicaragua; capitalism; debates and debating; history; labor laws & legislation; labour laws & legislation; peasants

The Forgotten Institution - Cangiani, Michele (International Review of Sociology, 2003)
Presents views of scholar Karl Polanyi on economic integration. Views of Polanyi on modern capitalist society; Distinction between external, local and internal markets by Polanyi. The three forms of economic integration include reciprocity, redistribution, and exchange. The article discusses Polyani's book "The Great Transformation," the development of market economies, the self-regulating market, some of the writings of Max Weber, big businesses, the efficiency of the market system, and social engineering.
History
Keywords: Great Transformation; The (Book); WEBER; Max; 1864-1920; big business; capitalism; international economic integration; social engineering

War and Social Change in Modern Europe: The Great Transformation Revisited - Halperin, Sandra (2003)
Halperin traces the persistence of traditional class structures during the development of industrial capitalism in Europe, and the way in which these structures shaped states and state behavior and generated conflict. She documents European conflicts between 1789 and 1914, including small and medium scale conflicts often ignored by researchers and links these conflicts to structures characteristic of industrial capitalist development in Europe before 1945. This book revisits the historical terrain of Karl Polanyi's The Great Transformation (1944), however, it argues that Polanyi's analysis is, in important ways, inaccurate and misleading. Ultimately, the book shows how and why the conflicts both culminated in the world wars and brought about a 'great transformation' in Europe. Its account of this period challenges not only Polanyi's analysis, but a variety of influential perspectives on nationalism, development, conflict, international systems change, and globalization.
History
Keywords: Great Transformation; The (Book); capitalism; class; critique; nationalism